Fashion sebagai Bentuk Ekspresi Diri dalam Komunikasi - Trisnawati, Tri Yulia (Universitas Semarang, 2011)
This study aims to determine self-expression through the values you want to appear in clothing consumption among adolescent girls as the main consumers of fashion products, to wear certain clothing types, and describes how to overcome obstacles that arise in expressing themselves through fashion. The research methodology used a qualitative descriptive method that focuses on observation and natural setting. Researchers acting as an observer, then create a category of behavior, observed symptoms, and record observations in a book. The research was conducted at the University of Semarang. The subjects in this study is the Student Department of Communication Class of 2008, FTIK, USM, while samples taken by 4 respondents with a purposive sampling technique. Fashion outline as an essential element of fashion and became the core of the interface itself for some adolescent girls, are used to convey messages with specific purposes to be conveyed by the wearer.